Penerapan Metode Line Balancing dengan Pendekatan Ranked Position Weight, Regional Approach, dan Largest Candidate Rules - Poncotoyo, Wahyu; Puspita, Sesaria Mardhiani Rachma; Zain, Muammar Fuad; Sholihah, Sita Aniisah; Ferdiansyah, Anton; Ayutia, Yolla (Jurnal Sistem Transportasi & Logistik, 2022)
Line Balancing is an assignment of a number of jobs into interconnected work stations in one line or assembly line with the aim of minimizing idle time on the hydraulic excavator assembly line, the assembly line specification has 27 work stations with 150 work elements. In the process of assembling the hydraulic excavator, there was an overtime that exceeded the takt time at work station 18 (BF 04), which resulted in the failure to achieve the production target of 5 units/day. One way to overcome this problem is to apply the line balancing method on the hydraulic excavator assembly line, the approach used is the Regional Approach, Ranked Positional Weight, and Largest Candidate Rules. Based on the analysis that has been done, it can be concluded that the Ranked Positional Weight approach has the best value with the number of work stations 18, line efficiency of 95.70%, balance delay of 4.30% and idle time of 66.84 minutes and also has good results. better than the initial conditions before the line balancing method was applied.